Composition and variability of the essential oils of the leaves and berries from Juniperus navicularis - Cavaleiro, C. (2003)
The compositions of the essential oils isolated from leaves and berries of Juniperus navicularis Gand., an endemic species from Portugal, were investigated by GC and GC-MS. Oils from representative samples of populations as well as from individual samples were studied. The oils consisted mainly of monoterpene hydrocarbons (67.1-88.0% and 61.7% for leaf and berry oils, respectively). [alpha]-Pinene (6.3-38.0%), limonene (7.0-34.6%), [alpha]-phellandrene (2.2-13.1%) and p-cymene (4.8-10.3%) were the major constituents of the oils from leaves and [beta]-myrcene (25.8%) and [alpha]-pinene (24.4%) the major ones of the oil from berries. No meaningful differences were observed comparing the composition of leaf oils from populations collected at distinct seasons but, within the same season, the range of variation of the major components suggests variability. Hierarchical clustering and principal component analysis (PCA) of the compositional data of the oils from individual samples confirms the variability allowing to establish two groups of essential oils differentiated by the content of the major constituents ([alpha]-pinene, limonene, [alpha]-phellandrene and E-nerolidol) and the ratios [alpha]-pinene/limonene.